Intervention Digital Medication Reminder App to Improve Hypertension Patient's Self-Management Medication Adherence - Selly Septi Fandinata; Eziah Ika Lubada; Ninik Mas Ulfa; Rizky Darmawan (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Among other chronic disorders, hypertension the most common chronic degenerative disease. Patient adherence to treatment is critical to the outcome of hypertension treatment. The provision of a digital medication reminder application intervention is one way to improve medication adherence. This study is to determine the impact of using digital smartphone applications to improve self-management of hypertensive patients. Quasi experimental with 2 prospective groups. The number of study samples was 408 patients. The results were descriptive, the control group had a pre post adherence level at the medium level of adherence, with 111 patients (60.66%) and 108 patients (59.02%). Intervention group at the level of adherence pre Middle 143 patients (63.56%), post 161 patients (71.56%) with a high level of adherence Mann Whitney test analysis, showed a significant change in the level of drug adherence in both groups p value of 0.000. Thus, digital smartphone applications can improve drug adherence.